Comparison of general and aesthetic effects between flapless and flap techniques in dental implantation: a meta-analysis of randomized controlled trials - Xiaomeng Gao; Siyu Qin; He Cai; Qianbing Wan (SpringerOpen, 2021)
Abstract Background Information about the aesthetic effects of flapless in implant surgeries is scant. Differences of the survival rate (SR) and crestal bone loss (CBL) between the two techniques were also controversial. Thus, this review was aimed to compare the general and aesthetic effects of flapless and flap approaches in implant surgeries. Materials and methods Following the principals of PRISMA, literature databases were searched for the eligible randomized controlled trials (RCTs) comparing the clinical performances of flap and flapless techniques. After that, relevant data of selected studies were pooled and analyzed to compare SR, bleeding on probing (BOP), probing depth (PD), visual analogue scale (VAS), papillae presentation index (PPI), keratinized mucosa (KM) width and CBL between the two techniques. Results Fourteen RCTs were included. No significant difference was found in SR (RR = − 0.01, 95% confidence interval (CI) (− 0.05, 0.04)), BOP (OR = 0.40, 95% CI (0.15, 1.02)), KM width (WMD = − 0.42, 95% CI (− 1.02, 0.17)) between two groups. Subgroup analysis revealed that the difference of CBL was insignificant in two groups (WMD = − 0.13, 95% CI (− 0.63, 0.38)). However, flap techniques would lead more peri-implant PD (WMD = − 0.37, 95% CI (− 0.51, − 0.23)). Subgroup analysis also indicated lower VAS scores in flapless group after 1 day (WMD = − 1.66, 95% CI (− 2.16, − 1.16)) but comparable pain experience after 3 days (WMD = − 0.59, 95% CI (− 1.33, 0.16)). Mean difference of PPI (WMD = 0.32, 95% CI (0.28, 0.35)) between the two groups was significant. Conclusions The flapless procedure showed a superiority in preserving gingival papillae, reducing postoperative pain and peri-implant PD compared to the flap procedure, while exhibiting comparable effects on SR, BOP, KW width changes and CBL. Flapless technique is more recommended at the ideal soft and hard tissue implanting sites.